The Smart City Concept in Gunungkidul Regency and its Impact on the Tourism Sector - Munandar, Siswoyo Aris (Universitas Terbuka, 2025)
The application of the Smart City concept has become an innovative solution in increasing the efficiency of urban management and the tourism sector. Gunungkidul Regency, which has great natural tourism potential, is starting to adopt this concept to increase tourist attractions and provide a better experience for tourists. This research aims to analyze the influence of Smart City implementation on the tourism sector in Gunungkidul Regency, with a focus on aspects of Smart Governance, Smart Economy, Smart Mobility, Smart Environment, Smart People and Smart Living. The research method used is a qualitative descriptive approach with literature study and analysis of secondary data from various sources such as government reports, scientific articles and digital media. The research results show that the implementation of Smart City has had a positive impact on the tourism sector, especially in increasing access to tourist information, improving the transportation system, increasing tourist comfort and safety, as well as encouraging local economic growth through the digitalization of tourism businesses. However, there are still several challenges in its implementation, such as limited digital infrastructure, low public digital literacy, and the need for large investments in technology development. Therefore, collaboration is needed between the government, the private sector and the community in optimizing the implementation of Smart City to support sustainable tourism growth in Gunungkidul Regency.